Application of Bio-pore Infiltration Hole as an Urban Runoff Management - Searphin Nugroho; Wahyono Hadi (IPTEK Journal of Proceedings Series, 2019)
The application of bio-pore infiltration holes (BIH) can be one solution for urban runoff management by reducing surface runoff to the ground. But, the difference in soil types and characteristics could affect the runoff reduction that can be achieved by BIH. This research aims to determine the runoff reduction can be achieved by bio-pore infiltration hole (BIH) from different soil types and conditions. The methods in this study mainly focus on hydraulic conductivity calculations using Porchet method and the implementation of Minister of Environment Regulation Numb. 12/2009 for the BIH installations. Based on the implementation of Minister of Environment Regulation Numb. 12/2009, the required BIHs for the area of 500 m2 are 1,000, both for silt and clay soils. The runoff reductions that can be achieved with the application of BIHs are 38.98 - 95.73% for silt soils and 20.67 - 54.28% for clay soils, depends on the soil conditions